Environmental Protection and Laws. - Jadhav, H. V. (Himalaya Pub. House, 2006)
Here is complete code on the Environmental Laws. It includes latest and up-to-date laws.: Environment Protection Act, 1986.; Environmental Protect Rules.; Laws Related with Water and Air Pollution.; Guidelines Issued by Government of India.; Code of Criminal Procedure and Environmental Protection.; Laws Related with Handling of Hazardous Chemicals.; Public Liability Insurance Act, 1991.